The Uneven Web: Digital Literacy, Access, and Exclusion in Marginalized India (Journal of Advances and Scholarly Researches in Allied Education, 2025)
Digital literacy is essential for social inclusion, economic advancement, and democratic engagement in contemporary society. Marginalised groups those hindered by poverty, location, gender, caste, handicap, or ethnicity continue to be disproportionately excluded from digital ecosystems. This research analyses digital literacy levels across marginalised areas, finds significant obstacles to digital inclusion, and evaluates current programs designed to close this gap. The research employs a mixed-methods approach, integrating a structured survey (n=400) with qualitative interviews and focus groups (n=50), revealing that digital exclusion is influenced by intersecting factors: economic limitations, infrastructural deficiencies, educational disparities, and gendered cultural norms. Despite the constraints of internet access, particularly among rural and low-income demographics, the lack of localised training and material is a significant impediment. The research underscores the significance of intersectional, community-oriented interventions and recommends particular governmental initiatives, such as investing in infrastructure, creating culturally appropriate training frameworks, and incorporating digital competencies into conventional schooling. Ultimately, digital literacy for marginalised populations is not a charitable endeavour but a structural need for fairness and inclusion in the digital age.